Characterization of a BODIPY Dye as an Active Species for Redox Flow Batteries. Issue 23 (16th November 2016) - Kosswattaarachchi, Anjula M.; Friedman, Alan E.; Cook, Timothy R.
Abstract: An all‐organic redox flow battery (RFB) employing a fluorescent boron‐dipyrromethene (BODIPY) dye (PM567) was investigated. In a RFB, the stability of the electrolyte in all charged states is critically linked to coulombic efficiency. To evaluate stability, bulk electrolysis and cyclic voltammetry (CV) experiments were performed. Oxidized and reduced, PM567 does not remain intact; however, the products of bulk electrolysis evolve over time to show stable redox behavior, making the dye a precursor for the active species of an RFB. A theoretical cell potential of 2.32 V was predicted from CV experiments with a working discharge voltage of approximately 1.6 V in a static test cell. Mass spectrometry was used to identify the products of bulk electrolysis. Related experiments were carried out using ferrocene and cobaltocenium hexafluorophosphate as redox‐stable benchmarks to further explain the stability results. The coulombic efficiency of a model cell using PM567 as a precursor for charge carriers stabilized around 73 %. Abstract : Bits & pieces : A redox flow battery employing a fluorescent borondipyrromethene (BODIPY) dye (PM 567) is investigated. A theoretical cell potential of 2.32 V is predicted from cyclic voltammetry (CV) experiments. To evaluate stability, bulk electrolysis and CV experiments together with UV/Vis absorbance spectroscopy are performed. Oxidized and reduced, PM 567 does not remain fully intact. However, the products of bulk electrolysis evolve over time to show stable redox behavior suitable for redox flow batteries.